Industrial accident - Crandall, William, 1956-; Parnell, John A. (John Alan), 1964-; Spillan, John E. ([London] : SAGE, 2016)
This case looks at the 2010 explosion of the Tesoro Corporation refinery in the United States. It shows how the resulting investigation discovered a host of health and safety violations in the company's history; it also demonstrates how ineffective enforcement of industry regulations can have far reaching consequences.
Originally Published in: Crandall, W. R., Parnell, J. A., & Spillan, J. E. (2013). Industrial Accident. In Crisis management: Leading in the new strategy landscape (2nd ed., pp. 131-135). Los Angeles: SAGE Publications, Inc. ISBN: 9781412991681.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Tesoro Petroleum Corporation; Industrial safety -- Management -- Case studies